Metaphor Is Between Metonymy and Homonymy: Evidence From Event-Related Potentials - Yurchenko, Anna; Lopukhina, Anastasiya; Dragoy, Olga (Frontiers in Psychology, 2020)
The goal of the present study was to investigate the interaction between different senses of polysemous nouns (metonymies and metaphors) and different meanings of homonyms, using the method of event-related potentials (ERPs) and a priming paradigm. Participants read two-word phrases containing ambiguous words and made a sensicality judgement. Phrases with polysemes highlighted their literal sense and were preceded by primes with either the same or different – metonymic or metaphorical – sense. Similarly, phrases with homonyms were primed by phrases with a consistent or inconsistent meaning of the noun. The results demonstrated that polysemous phrases with literal senses preceded by metonymic primes did not differ in ERP responses from the control condition with the same literal primes. In contrast, processing phrases with the literal sense preceded by metaphorical primes resulted in N400 and P600 effects that might reflect a very limited priming effect. The priming effect observed between metonymic and literal senses supports the idea that these senses share a single representation in the mental lexicon. In contrast, the effects observed for polysemes with metaphorical primes characterize lexical access to the word’s target sense and competition between the two word senses. The processing of homonyms preceded by the prime with an inconsistent meaning, although it did not elicit an N400 effect, was accompanied by a P600 effect as compared to the control condition with a consistent meaning of the prime. We suppose that the absence of the N400 effect may result from inhibition of the target meaning by the inconsistent prime, whereas the P600 response might reflect processes of reanalysis, activation and integration of the target meaning. Our results provide additional evidence for the difference in processing mechanisms between metonymies and metaphors that might have separate representations in the mental lexicon, although they are more related as compared to homonyms.